Understanding the impact of Russian wheat aphid-associated microbes on plants - Luna, Emily K., author; Leach, Jan E., advisor; Borlee, Brad, committee member; Nalam, Vamsi, committee member; Trivedi, Pankaj, committee member (Colorado State University. Libraries, 2025)
Plant-insect-microbe interactions shape the outcome of plant defense responses, yet the role of aphid-associated bacteria in modulating host susceptibility remains largely unexplored. This dissertation investigates the influence of bacterial communities associated with the Russian wheat aphid (RWA, Diuraphis noxia) on plant responses, focusing on barley and wheat as plant host systems. Through a combination of proteomics, microbiome analysis, transcriptomics and biological assays, this work provides novel insights into how aphid-associated microbes contribute to the amount of damage aphids cause to plants (aggressiveness) and alter plant hormone signaling. In Chapter 2, proteomic and microbiome analyses reveal that the saliva of RWA is enriched with bacterial proteins, predominantly from Enterobacteriaceae. Several bacteria genera were isolated from aphids and wheat plants only after aphid feeding, suggesting horizontal transmission of microbes during infestation. Experimental reduction of bacterial populations in aphids led to decreased chlorosis in wheat, providing direct evidence that aphid-associated bacteria enhance aphid aggressiveness. Chapter 3 characterizes a novel aphid-associated bacterial species, Winslowiella iniecta (previously, Erwinia iniecta) isolated from RWA and identified through multilocus sequence analysis and whole genome sequencing. While W. iniecta was not pathogenic to plants, its presence influenced aphid performance, suggesting an indirect role in aphid fitness and plant interactions. Chapter 4 demonstrates that honeydew is the primary source of aphid-acquired bacteria. Using RNA-sequencing and network analysis, we show that bacterial-enriched honeydew significantly alters barley defense pathways, particularly by modulating salicylic acid (SA) and jasmonic acid (JA) signaling. Barley plants infiltrated with honeydew from bacteria-rich aphid colonies exhibited stronger transcriptomic responses, characterized by enhanced SA activation alongside simultaneous JA suppression and degradation. We purpose a model in which aphids acquire bacteria by feeding on honeydew-contaminated leaves. As they probe and feed, bacteria or bacterial proteins are introduced into the plant via the stylet, where they interact with plant cells, leading to SA upregulation and JA suppression. Collectively, this dissertation advances our understanding of plant-aphid-microbe interactions, identifying bacterial contributions to aphid aggressiveness and demonstrating previously unrecognized role of honeydew in shaping plant defense responses to RWA. These findings have implications for the development of aphid management strategies, particularly in breeding crops with enhanced resilience to aphids.